Revascularization and Apical Plug in an Immature Molar - Roghanizadeh, Leyla; Fazlyab, Mahta (Iranian Endodontic Journal, 2019)
Managing of necrotic permanent teeth with immature apices is a treatment challenges. Treatment of such teeth includes apexification, apical plug and more recently, revascularization technique with the probable advantage of continuation of root development. In the present case report the referred patient had discomfort with a necrotic immature mandibular first molar. Periapical radiography showed a rather large apical lesion around immature roots. Revascularization protocol using calcium-enriched mixture (CEM) cement was indicated for the mesial root. However, in distal canal apical plug technique was applied. At 2-year follow-up, both procedures were successful in relieving patient’s symptoms. Dentin formation and increase in length of the mesial root was obvious. Apical plug and revascularization technique proved to be successful in management of necrotic immature teeth; moreover, revascularization carried the advantage of continuation of root development. Keywords: Apexification; Apical Plug; Calcium-enriched Mixture Cement; CEM Cement; Endodontics; Regeneration; Revascularization